Positive effects of a Clostridium butyricum-based compound probiotic on growth performance, immune responses, intestinal morphology, hypothalamic neurotransmitters, and colonic microbiota in weaned piglets. Issue 5 (9th May 2019) - Cao, Guangtian; Tao, Fei; Hu, Yuhua; Li, Zhanming; Zhang, Yan; Deng, Bo; Zhan, Xiu'an
Abstract : Weaning stress in piglets can lead to poor health outcomes and reduced production. Abstract : Weaning stress in piglets can lead to poor health outcomes and reduced production. We investigated the effects of probiotics, one potential antibiotic alternative, on the growth performance, serum biochemical parameters, intestinal morphology, mucosal immunity, hypothalamic neurotransmitters, and colonic microflora in weaned piglets. Thirty-six weaned piglets were fed a basal diet, a diet supplemented with colistin sulphate antibiotic, or a diet supplemented with probiotics including Clostridium butyricum, Bacillus subtilis, and B. licheniformis . Probiotics significantly increased the feed : gain ratio, improved the average day gain from day 1 to day 28, and decreased the diarrhoea index. Probiotics also lowered the serum concentrations of AST, ALT, and ALP on day 14 and lowered the serum concentration of ALT on day 28 compared with the control. Probiotic supplementation caused fewer ileal apoptotic cells. The serum and ileal concentrations of TNF-α and IL-1β on day 28 were significantly lowered, and the serum concentrations of IL-6 were significantly lowered on days 14 and 28. Probiotic-fed piglets exhibited higher contents of hypothalamic serotonin and dopamine as well as serum γ-aminobutyric acid along with higher colonic concentrations of butyrate and valerate on day 28. High-throughput sequencing showed 972 core operational taxonomic units among all groups, of which 48 were unique to the probiotic-treated group. The relative abundance of genus Bacillus and species Bacillus velezensis was enriched in probiotic piglets; the phylogenetic investigation of communities by the reconstruction of unobserved states indicated that amino acid metabolism, DNA repair, replication and recombination proteins, and secretion systems were enriched with probiotics. In conclusion, the Clostridium butyricum -based probiotics improved growth performance, enhanced intestinal morphology, changed hypothalamic neurotransmitters and modulated colonic microflora in weaned piglets.